Two-dimensional photonic crystals for engineering atom–light interactions - Yu, Su-Peng (Proc Natl Acad Sci U S A, 2019)
We present a 2D photonic crystal system for interacting with cold cesium (Cs) atoms. The band structures of the 2D photonic crystals are predicted to produce unconventional atom–light interaction behaviors, including anisotropic emission, suppressed spontaneous decay, and photon-mediated atom–atom interactions controlled by the position of the atomic array relative to the photonic crystal. An optical conveyor technique is presented for continuously loading atoms into the desired trapping positions with optimal coupling to the photonic crystal. The device configuration also enables application of optical tweezers for controlled placement of atoms. Devices can be fabricated reliably from a 200-nm silicon nitride device layer using a lithography-based process, producing predicted optical properties in transmission and reflection measurements. These 2D photonic crystal devices can be readily deployed to experiments for many-body physics with neutral atoms and engineering of exotic quantum matter.